Android app for medical consultation - Tan, Johan Ngiap Han (2018)
Current e-medical consultation services are either completely automated or semi-automated. Fully automated e-medical consultation services tend to be useful for a group of people who have common illness symptoms. Symptoms that are more severe will require physical examination by a doctor to understand the situation and to give proper diagnosis. Automated e-medical consultation services will not be able to give the best diagnosis or would recommend patients to visit the nearest doctor immediately to identify the cause of the symptom. Semi-automated e-medical services utilize technology to smoothen the flow of medical consultation such as video calling a doctor who is available. However, such practices are costly in terms of building the system and will require a relatively large number of doctors to be readily available for the system to be efficient. Patients may still be required to go to the nearest doctor to have their symptom identified if the symptom is unable to be verified through the video call. Current semi-automated e-medical consultation services have not investigated a subset of the automation service which is collection of user input data through technology. By interacting with a chatbot which is somewhat like a doctor, the flow of how a doctor identifies your symptoms can be hastened by a considerable amount of time. This project aims to reduce the amount of time required by doctors to ask patients questions related to their symptoms. The questions will be mostly asked by a chatbot and recorded down into the system and doctors can retrieve the patient’s record almost instantly via the application. This in return will reduce the time required for consultation for common symptoms and quickly process patients who just need medication compared to patients who need more medical attention.